2015
DOI: 10.3402/tellusb.v67.25531
|View full text |Cite
|
Sign up to set email alerts
|

One-year measurement of size-resolved particle fluxes in an urban area

Abstract: Size-resolved particle flux measurements were carried out in an urban area from April 2012 to April 2013. Together with a standard eddy covariance system, two fast optical particle counters have been employed on a 65-meter-high tower in Mu¨nster, Germany. Particle number fluxes were directly calculated for particles with diameters from 0.06 to 10 mm within 16 individual size-bins. Whereas particle number concentrations show a distinct yearly pattern with maxima in winter and minima in summer, the flux time ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 46 publications
4
13
0
Order By: Relevance
“…Most studies having measured particle flux from this technique focused on the quantification of the flux itself and not on its analogy with momentum or heat fluxes. These studies were mainly performed over urban areas (Deventer, El‐Madany, et al, ; Dorsey et al, ; Ma˙rtensson et al, ), vegetated surfaces (Damay et al, ; Deventer, Held, et al, ), and much less over desert areas (Fratini et al, ; Porch & Gillette, ). The only studies comparing particle and heat turbulent transports either observed similarity between both scalars (Fratini et al, ; Ma˙rtensson et al, ) or assumed similarity to correct their particle flux from the heat flux due to the slow response time of their particle counter (Damay et al, ; Deventer, Held, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies having measured particle flux from this technique focused on the quantification of the flux itself and not on its analogy with momentum or heat fluxes. These studies were mainly performed over urban areas (Deventer, El‐Madany, et al, ; Dorsey et al, ; Ma˙rtensson et al, ), vegetated surfaces (Damay et al, ; Deventer, Held, et al, ), and much less over desert areas (Fratini et al, ; Porch & Gillette, ). The only studies comparing particle and heat turbulent transports either observed similarity between both scalars (Fratini et al, ; Ma˙rtensson et al, ) or assumed similarity to correct their particle flux from the heat flux due to the slow response time of their particle counter (Damay et al, ; Deventer, Held, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We expect to develop further understanding of droplet growth mechanisms in natural clouds and fog. For example, the observation of bidirectional fluxes in fog lead to new questions of temporal limitations of droplet growth and evaporation mechanisms [71][72]. It is not unlikely that these bidirectional fluxes of microdroplets can be supported by electric fields that are typically present near the Earth's surface [11,70].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, measurements were made with fast laser-based optical particle spectrometers, typically covering the size range 0.1-1 μm Nemitz et al 2002;Sievering 1983Sievering , 1987) and more recently 0.25-2.5 μm (Ahlm et al 2010;Vogt et al 2011) and down to 0.06 μm (Deventer et al 2011;Harrison et al 2011). A range of aerodynamic and electromobility spectrometers have also now been used (Damay et al 2009;Grönholm et al 2007;Nemitz et al 2000a;Pryor 2006;Pryor et al 2009;Schmidt and Klemm 2008).…”
Section: Measurementsmentioning
confidence: 99%
“…Urban flux measurements represent the emission from combustion sources and (wind-driven and vehicle induced) resuspension (Deventer et al 2011;Dorsey et al 2002;Järvi et al 2009;Martin et al 2008;Schmidt and Klemm 2008;Vogt et al 2011). There are clearly situations in which emissions take place.…”
Section: Interpretation Of Emission and Fast Deposition Fluxesmentioning
confidence: 99%